Effect of a c-Met-specific, ATP-competitive small-molecule inhibitor SU11274 on human ovarian carcinoma cell growth, motility, and invasion. Issue 5 (1st August 2008) - Koon, E. C.; Ma, P. C.; Salgia, R.; Welch, W. R.; Christensen, J. G.; Berkowitz, R. S.; Mok, S. C.
Abstract : Increased expression of the receptor tyrosine kinase c-Met has been shown to correlate with enhanced cell proliferation, motility, and invasion. The objectives of this study were to characterize total and activated c-Met expression in both normal and malignant human ovarian epithelial cells and to determine the effects of inhibiting the activation of c-Met on ovarian epithelial cell growth, motility, and invasion. Total c-Met was overexpressed in 82 (68%) of 119 ovarian carcinomas, as shown by immunohistochemistry. Quantitative reverse transcription–polymerase chain reaction and Western blot analyses revealed that ovarian carcinoma cell lines had higher levels of c-Met messenger RNA, total protein, and activated protein expression compared to normal ovarian epithelial cell cultures. Using a specific adenosine triphosphate-competitive small-molecule inhibitor, SU11274, activated c-Met was decreased in normal and ovarian carcinoma cell lines. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assays showed that cell growth inhibition directly correlated to the level of activated c-Met detected in each cell line ( r =−0.87, P = 0.012). Using modified Boyden chamber assays, ovarian carcinoma cells treated with SU11274 demonstrated significantly decreased cell motility and invasion compared to untreated cells ( P = 0.003 and P < 0.001, respectively). These data indicate that c-Met is overexpressed in the majority of malignant ovarian epithelial cells both In vivo and in vitro and that decreasing activated c-Met in vitro can significantly decrease ovarian carcinoma cell growth, motility, and invasion. Developing therapies that specifically inhibit the activation of c-Met may represent a novel therapeutic modality for patients with ovarian carcinomas expressing high levels of c-Met.